REVOLUTIONIZING URBAN LAST-MILE DELIVERY WITH AUTOMATED PARCEL LOCKERS: AN OVERVIEW - Anca POPESCU; Adriana TULBURE (Annals of the University of Oradea: Economic Science)
With last-mile logistics being the most important component of delivery, the rapid growth of electronic commerce has also led to a surge in logistical complexity. Because users prefer to have their purchases delivered to their homes, this is one of the biggest challenges facing e-commerce. Many times, deliveries cannot happen because the recipients are not at the agreed delivery point. This causes the quality of service to decrease and distribution costs to increase. Based on this information, the present paper studies the role which Automated Parcel Lockers (APLs) have in addressing flaws in the urban last-mile delivery system. It is clear that e-commerce is on an ascending path, continuously developing, while traditional methods of delivery often encounter challenges such as high costs, increased impact on the environment, or customer dissatisfaction. APLs are part of a promising solution offering advantages such as improved delivery efficiency and customer satisfaction while reducing carbon emissions. The research methodology included a review of the literature on the subject, examination of industry reports and various case studies. The results provided an ambivalent perspective of both advantages and challenges which this system of delivery provides. Among the benefits, operational cost savings and reduced environmental impact are worth mentioning, while the challenges bring forward matter such as high installation costs or accessibility concerns. The findings also suggest that APLs require, for a successful integration in logistic operations, overcoming barriers of a technical and financial nature. The paper concludes with a broad perspective on the future development of APLs and necessary research directions. The importance of investigating further technological integration of these means, while adapting to both urban and rural conditions is also emphasized.